Design, Molecular Docking, ADMET Studies, Synthesis, Characterization, and Antimicrobial of Nicotinamide Derivatives via Mannich reaction - Sager, Athra G.; Abaies, Jawad Kadhim; Katoof, Zeena R. (Iraqi Journal of Science, 2025)
In this study, a series of novel Mannich bases were synthesized by the conjugation of Vitamin B3 with the medicinal compound sulfamethoxazole. Five Schiff base compounds were prepared via a condensation reaction involving five different aldehydic precursors. Additionally, a compound incorporating an aromatic thiadiazine ring was synthesized. The prepared compounds were characterized using FT-IR, 1H and 13CNMR spectrometric methods, and melting point measurements. Molecular docking studies were performed to investigate the interactions of the synthesized compounds with three specific bacterial protein targets, namely: 4H2M from Escherichia coli, 3FYV from Staphylococcus aureus, and 6P4T from Salmonella Besides. Docking simulations showed that all the prepared compounds exhibited hydrophilic interactions with the target proteins by forming hydrogen bonds. The formation of rings and arenes aromatics in molecular structure facilitated water softened interactions between drugs and bacterial proteins. The biological activity of these prepared compounds was investigated against five classes of bacteria, negative and positive grams. The obtained results showed a significant activity compared to sulfamethoxazole medication. On the other hand, absorbed and poisoning of the prepared compounds were examined using the Swiss ADME tool. The yielded results showed that all ligands did not fulfill Lipinski’s rule, except compound M (Mannich compound). This could be attributed to the large area and the high molecular weight of the compounds which were more than 500g/mol.